2022
DOI: 10.1111/sjop.12850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of work‐to‐family enrichment on psychological distress and family satisfaction: A dyadic analysis in dual‐earner parents

Abstract: Resources that individuals acquire at work can have significant effects on their own well‐being and family satisfaction, and on those of their closest family relations. Following the conservation of resources theory, this study examined the effects of work‐to‐family enrichment (WFE) on psychological distress (depression, anxiety, and stress) and family satisfaction (SWFaL) in different‐gender dual‐earner parents. The sample consisted of 473 couples – mother and father – from Temuco, Chile, who answered the Wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 73 publications
3
10
1
Order By: Relevance
“…According to Carnes (2017), most women still feel social pressure to uphold their duties in the domestic sphere as they use their coping mechanisms to reduce the impact of role overload from family demands, but men usually use their coping resources to mask their role conflict-that is, the impact of conflicting role expectations. Likewise, Orellana et al (2022) reported that although personal resources of both members of the couple increase their level of family satisfaction, gender differences emerge. Fathers' affective resources reduce their own psychological distress, whereas mothers tend to acquire cognitive skills that are directly invested in improving family functioning.…”
Section: Coping Wf Conflict and Emotional Exhaustion At The Couple Levelmentioning
confidence: 99%
“…According to Carnes (2017), most women still feel social pressure to uphold their duties in the domestic sphere as they use their coping mechanisms to reduce the impact of role overload from family demands, but men usually use their coping resources to mask their role conflict-that is, the impact of conflicting role expectations. Likewise, Orellana et al (2022) reported that although personal resources of both members of the couple increase their level of family satisfaction, gender differences emerge. Fathers' affective resources reduce their own psychological distress, whereas mothers tend to acquire cognitive skills that are directly invested in improving family functioning.…”
Section: Coping Wf Conflict and Emotional Exhaustion At The Couple Levelmentioning
confidence: 99%
“…Regarding resource support from FSL, employees can produce and develop all kinds of personal resources, such as physical, emotional and psychological resources (Bagger and Li, 2014;Chambel et al, 2022). When the demand for autonomy and capacity is satisfied, it not only complements the resources but can also alleviate anxiety, stress and depression (Orellana et al, 2022;Hao et al, 2022). The RGD framework holds that most individuals have the instinct to grow, develop and pursue the highest quality of life in systems, including organisations and families (Wayne et al, 2007;Demerouti et al, 2013).…”
Section: Mediating Role Of Psychological Distressmentioning
confidence: 99%
“…When employees feel CMS 18,3 a positive spillover from work to family, they are more inclined to think that they have sufficient resources and abilities to improve the quality of life in the receiving field. This can improve employees' mental health and reduce negative psychological states such as depression and anxiety (Orellana et al, 2022), broadening the ability of individuals to take effective actions, thus increasing their tendency to actively change their behaviours (Zhou et al, 2021). In addition, the meta-analysis of McNall et al (2010) demonstrated that WFE would generate resources to improve employees' ability to mitigate the challenges in balancing work and family relationships.…”
Section: Serial Mediating Effect Of Work-family Enrichment and Psycho...mentioning
confidence: 99%
“…In this region, culture and the still-present traditional gender roles may account for different work-family interface experiences and effects between fathers and mothers than those previously reported in developed countries. This approach fills in the gaps in the literature and adds new insights into the relationship between FtoWC and job satisfaction [16][17][18].…”
Section: Introductionmentioning
confidence: 96%